2015
DOI: 10.7763/joebm.2015.v3.177
|View full text |Cite
|
Sign up to set email alerts
|

National Cultural Distance and International Acquisition Performance

Abstract: Abstract-This paper investigates the implications of national cultural distance on international acquisition performance, involving companies from England. It proposes recommendations for the managers of English companies in how to manage these differences effectively. In general, findings indicate that the differences in national culture obstruct integration capabilities, bringing about a negative indirect effect on acquisition performance. From these findings, our recommendations are established, which sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…to the effects of independent and control variables in international acquisition performance and to distinguish between direct and interaction effect (Table 4) Drawing on the knowledge-based perspective, the dimensions of knowledge transfer, cultural dynamics, and organizational strategic compatibility are determined in this study to be crucial for understanding such inquiries (Akanni & Ahammad, 2015;Easterby-Smith et al, 2008;Lyes & Salk, 2007;Perez-Nordtvedt et al, 2008;Reus & Lamond, 2009 (Park et al, 2009). However, the result of their efforts has been unclear.…”
Section: Hierarchical Regression Analysis Was Usedmentioning
confidence: 96%
See 1 more Smart Citation
“…to the effects of independent and control variables in international acquisition performance and to distinguish between direct and interaction effect (Table 4) Drawing on the knowledge-based perspective, the dimensions of knowledge transfer, cultural dynamics, and organizational strategic compatibility are determined in this study to be crucial for understanding such inquiries (Akanni & Ahammad, 2015;Easterby-Smith et al, 2008;Lyes & Salk, 2007;Perez-Nordtvedt et al, 2008;Reus & Lamond, 2009 (Park et al, 2009). However, the result of their efforts has been unclear.…”
Section: Hierarchical Regression Analysis Was Usedmentioning
confidence: 96%
“…However, existing understandings of how and when knowledge is best transferred for the benefit of international acquisitions is rather limited. For instance, studies have resulted in inconsistent findings on the impact of organizations' nationality and corporate cultural differences on international acquisition (Akanni & Ahammad, 2015;Ahammad & Glaister, 2009;Perez-Nordtvedt, Kedia, Datta, & Rasheed, 2008). Numerous empirical studies have also revealed that organizational differences in nationality and corporate culture have a negative effect on international acquisition performance, while other studies have shown quite the opposite or have had mixed results (Ahammad, Tarba, & Glaister, 2016;Sarala & Vaara, 2010;Slangen, 2006;Vaara, Sarala, Stahl, & Bjorkman, 2012).…”
Section: ⅰ Introductionmentioning
confidence: 99%